O lúdico e a educação ambiental na formação de professores: diálogos possíveis - EVANGELISTA, Larissa de Mello (2009)
This work presents the results of research done with students of higher education in an attempt to join the playful to the theme of Environmental Education as a proposal to improve the teaching-learning process of future teachers of science and biology, as well as its responsiveness with respect to Environmental Education, thus enabling a new alternative for the teacher to work in their classes. Thus, we work with a class of Bachelor's course in Biological Sciences at a state university in the city of Itapuranga, Goiás, Brazil whose students are in their third year. The method used was action-researchparticipatory, since the research in the classroom in which the researcher is the teacher of the discipline, whose results will be worked on improving the teaching-learning process. To conduct this research the class consisting of 32 students was divided into two groups, and each one in 3 sub-groups, in which one of them would have To consider Resolution an environmental problem caused by the Sugar-Alcohol Plant in the city and the other to create an Environmental Consulting Company to resolve an Environmental problem in the city, with name, symbol, slogan, advertising, etc.. According to the survey were six criteria for analysis: Identification of the problem, interest / motivation, Competition, Creativity, and Problem Resolution and Personification. The results of this research show that recreational activities can be worked in environmental education issues and effective manner, because in addition to increasing the interest is a motivating activity, brings together students, requires freedom of action, increases the disciplinary aspect and finally, very helpful in improving the teaching-learning process